Penicillin- and third-generation cephalosporin-resistant strains of Streptococcus pneumoniae meningitis: Case report and literature review. Issue 5 (May 2022) - Ishikawa, Kazuhiro; Matsuo, Takahiro; Suzuki, Takahiro; Kawai, Fujimi; Uehara, Yuki; Mori, Nobuyoshi
Abstract: Background: Treatment of patients with penicillin-resistant S. pneumoniae (PRSP) is complicated because of the relatively poor blood-brain barrier penetration of effective antimicrobials. Our case: A previously healthy 70-year-old woman, a traveler from China to Japan, was admitted to our hospital with fever and loss of consciousness. She has no history of pneumococcal vaccination. She was diagnosed with bacterial meningitis due to penicillin-and third-generation cephalosporin-resistant strains of S. pneumoniae . The patient was successfully treated with a combination therapy of vancomycin (VCM) and levofloxacin (LVFX) and recovered without any neurological sequelae. As the treatment of penicillin-and third-generation cephalosporin-resistant strains of S. pneumoniae meningitis remains unclear, we conducted a review of the reported cases of meningitis caused by penicillin- and cephalosporin-resistant S. pneumoniae . Method: We performed a search using the keywords "penicillin-resistant Streptococcus pneumoniae, " "meningitis, " and "pneumococcal meningitis". We searched the electronic databases PubMed, Embase, and Ichushi from their inception to March 2020. Subsequently, two authors independently reviewed the resulting database records, retrieved full texts for eligibility assessment, and extracted data from these cases. Result: We identified 18 papers describing thirty-five cases of penicillin- and cephalosporin-resistant S. pneumoniae meningitis including our case. The patient's characteristics were; median age: 50 years, men:50%, 85% of cases received combination regimens of antibiotics: Ceftroriaxone (CTRX) plus VCM (20 cases), CTRX plus VCM plus rifampicin (RFP) (two cases), CTRX plus linezolid (one case), fluoroquinolones (two cases), carbapenems (six cases), Thirty-five percent received steroids. Twenty-four percent of patients died. Twenty-six percent of patients complicated neurological sequalae. Conclusion: Combination therapy including VCM plus LVFX could be a treatment option.